Stress and Stress Managements of Women Who Had Lost their Husbands During Pregnancy from the Situation of Unrest in Three Southern Border Provinces - เลาะนะ, นิอารีซะห์; ชูนวล, โสเพ็ญ; อินทนนท์, ถนอมศรี; แก้วพิมล, ปรียา (Princess of Naradhiwas University Journal, 2018)
This descriptive qualitative research aimed to explore stress and stress management of women who had lost their husbands during pregnancy from the situation of unrest in the three southern border provinces of Thailand. Fifteen participants were selected by purposive sampling. In-depth interviews were conducted for data collection. Data analysis was carried out through content analysis. Member checking was conducted to establish the rigor of the study. The findings revealed two themes of stress and stress management of women who had lost their husbands during pregnancy from the situation of unrest in three southern border provinces. The first theme was response after loss of husband; there were 3 categories: (1.1) perceiving of the loss, (1.2) duration of coming to terms, and (1.3) point of deciding to change management. The second theme was stress managementconsisting of 2 categories: (2.1) management by oneself, and (2.2) management with support from others. Thefindings of this study provide understanding about stress and stress management of women who had lost their husbands during pregnancy from the situation of in three southern border provinces. The study has provided basic knowledge and understanding of the context of women who had lost their husband. Health personnelcan provide beneficial support to these women that can improve their quality of life.